2015
DOI: 10.1007/s10461-015-1066-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Associated Sexual and Substance Use Behaviors Among Men Who Have Sex with Men in Moscow, Russia

Abstract: Introduction Alcohol use is a public health problem in the Russian Federation. This study explored relationships between alcohol use and behavioral risks for HIV transmission among men who have sex with men (MSM) in Moscow, Russia. Methods Alcohol Use Disorder Identification Test scores for 1,367 MSM participating in a cross-sectional survey and HIV testing were categorized to: “abstinence/low use”, “hazardous use”, “harmful use/dependency”. Multiple logistic regression models compared dependent variables fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
4
16
0
4
Order By: Relevance
“…Compared to regular drinkers, hazardous/harmful drinkers were four times less likely to report consistent condom use (11% vs. 44%). Our findings were consistent with recent research showing that the odds of having multiple sexual partners and engaging in inconsistent condom use were higher for hazardous/harmful drinkers relative to abstinent/low-level drinkers living in Russia [40]. Reducing hazardous/harmful alcohol use may be a key consideration in reducing sexual transmission of HIV among Russians.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to regular drinkers, hazardous/harmful drinkers were four times less likely to report consistent condom use (11% vs. 44%). Our findings were consistent with recent research showing that the odds of having multiple sexual partners and engaging in inconsistent condom use were higher for hazardous/harmful drinkers relative to abstinent/low-level drinkers living in Russia [40]. Reducing hazardous/harmful alcohol use may be a key consideration in reducing sexual transmission of HIV among Russians.…”
Section: Discussionsupporting
confidence: 91%
“…[6]. Briefly, Syphilis infection was measured with Lues rapid plasma reaction (RPR) (Nearmedic Plus, Moscow, Russia) and those samples testing positive for syphilis were confirmed with Lues RPGA test (Nearmedic Plus, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…While recent epidemiologic investigations have demonstrated high-risk sexual behaviours and high 15% HIV prevalence among Moscow-based MSM, substantially higher than the 1% prevalence of the general adult population, HPV infection has not been a focus of research or public health surveillance among MSM in the Russian Federation. [610] Currently, no estimates are available on the proportion of anal cancers that may be attributable to HPV in the Eastern Europe Central Asia (EECA) region, but other modelling estimates from the Eurostat cancer data suggest that of 72,694 new cancer cases each year among European men, 17,403 of these could be attributable to HPV and 15,497 attributable to high-risk HPV genotypes. [11] Approximately 30% of all new annual European cancer cases attributable to HPV16/18 are estimated to occur in men.…”
Section: Introductionmentioning
confidence: 99%
“…While rates have remained low and relatively stable across much of western and central Europe, with rates rarely above 4% ever having injected,4 5 this drug delivery method has been shown to be more common in central Asia,6 Russia7 and parts of Sub-Saharan Africa 8. Analysis of community survey data from 2011 in Sydney, Australia, found that 5.0% of MSM had injected drugs within the previous 6 months, a figure that is considerably higher than among the general population 9…”
Section: Patterns Of Substance Use Among Msmmentioning
confidence: 99%